2016
DOI: 10.1111/napa.12090
|View full text |Cite
|
Sign up to set email alerts
|

Disaster response and recovery: Aid and social change

Abstract: This article offers a discussion of the complex and far‐reaching impacts that disaster aid has on the socio‐ecological and cultural‐political transformation of affected communities through three different and interrelated theoretical and ethnographic angles presented in the “Response and Recovery” section of the plenary session on the anthropology of risk, hazards, and disasters. It introduces the research on “disaster narratives,” the framing of “bad victims,” and state‐led recovery of ethnic cultures by Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…In the most startling examples of the homogenization of culture and people in disaster contexts, we have cultural commodification (Zhang ) and co‐option (Faas , ). Qiaoyun Zhang () discusses the 8.0 magnitude earthquake in the southwestern Sichuan province of China that, in 2008, resulted in the deaths of upwards of 70,000 people, including nearly 20,000 from the Qiang ethnic minority. Following the earthquake, the Chinese government made special efforts to rebuild Qiang communities and invest significant resources into this area, especially as a mechanism to build state identity.…”
Section: Vulnerability and The Fight Against Homogenizationmentioning
confidence: 99%
“…In the most startling examples of the homogenization of culture and people in disaster contexts, we have cultural commodification (Zhang ) and co‐option (Faas , ). Qiaoyun Zhang () discusses the 8.0 magnitude earthquake in the southwestern Sichuan province of China that, in 2008, resulted in the deaths of upwards of 70,000 people, including nearly 20,000 from the Qiang ethnic minority. Following the earthquake, the Chinese government made special efforts to rebuild Qiang communities and invest significant resources into this area, especially as a mechanism to build state identity.…”
Section: Vulnerability and The Fight Against Homogenizationmentioning
confidence: 99%
“…Experts working for state agencies and NGOs (however well-meaning) can and often do exacerbate vulnerabilities and (re)produce inequalities in response and recovery efforts by marginalizing local knowledge and capacities in favor of their own expertise (e.g., Gamburd 2013; Marchezini 2015;Zhang 2016). At times, even sincere efforts of culturally sensitive humanitarian action fail because experts misread local culture as homogenous, scripted, and uncontested, and expect that local practices can be readily appropriated for organizational objectives (Faas and Barrios 2015;Maldonado 2016).…”
Section: Cooperation Time: the Discipline Of Minga Practicementioning
confidence: 99%
“…The appropriation of local practices to realize organizational goals can facilitate the internalization of dominant ideologies; people may come to invoke local values in ways that nonetheless articulate with dominant interests and thereby police themselves based on expert rules of conduct. Thus, on another level, politically charged "metafunctions of humanitarian action" serve as puissant conduits of dominant ideologies and practices (Donini 2008); experts impose the rationalities of organizational priorities, manage populations, and distinguish the deserving from the undeserving (Faas n.d.;Gamburd 2013;Marchezini 2015;Zhang 2016).…”
Section: Cooperation Time: the Discipline Of Minga Practicementioning
confidence: 99%
“…Disaster intervention and disaster aid confers power on the giver to decide and shape forms of post-disaster development. Portrayals of affected communities and the inherent biases within them (e.g., deserving versus undeserving aid recipients) may reinforce hegemonic/economic relations and discursively create certain channels for intervention prioritized by the donor (Zhang, 2016). Similarly, Drake (2016) finds that governmental bodies set up to manage the impacts of disaster may represent poorer disaster-affected populations in a blanket way as uninformed and manipulated by activists, despite an evident diversity of viewpoints on the ground.…”
Section: The Characterization Of Actors: Power and Agendamentioning
confidence: 99%
“…In the discussion that follows, we synthesize insights from the relatively limited body of research that exists on representational aspects of disaster recovery to explore further how dominant ways of thinking, and challenges to these, influence the support disasteraffected people receive, their capacities to recover, and their rights and agency in these processes. We also examine disaster-affected sustained period (anderson and Woodrow, 2019;Zhang, 2016). Several decades of critical research on disaster risk have amply demonstrated that vulnerability to disaster impacts is conditioned as much by social factors as it is by the nature of the physical hazards that trigger the destructive events (e.g., Cutter, 1996;Hewitt, 1983;Wisner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%